Production process and optimization of solid bioethanol from empty fruit bunches of palm oil using response surface methodology - Nurfahmi; Mofijur M.; Ong H.C.; Jan B.M.; Kusumo F.; Sebayang A.H.; Husin H.; Silitonga A.S.; Mahlia T.M.I.; Rahman S.M.A. (MDPI AG, 2023)
This study aimed to observe the potential of solid bioethanol as an alternative fuel with high caloric value. The solid bioethanol was produced from liquid bioethanol, which was obtained from the synthesis of oil palm empty fruit bunches (PEFBs) through the delignification process by using organosolv pretreatment and enzymatic hydrolysis. Enzymatic hydrolysis was conducted using enzyme (60 FPUg-1 of cellulose) at a variety of temperatures (35 C, 70 C, and 90 C) and reaction times (2, 6, 12, 18, and 24 h) in order to obtain a high sugar yield. The highest sugars were yielded at the temperature of 90 C for 48 h (152.51 mg/L). Furthermore, fermentation was conducted using Saccharomyces cerevisiae. The bioethanol yield after fermentation was 62.29 mg/L. Bioethanol was extracted by distillation process to obtain solid bioethanol. The solid bioethanol was produced by using stearic acid as the additive. In order to get high-quality solid bioethanol, the calorific value was optimized using the response surface methodology (RSM) model. This model provided the factor variables of bioethanol concentration (vol %), stearic acid (g), and bioethanol (mL) with a minus result error. The highest calorific value was obtained with 7 g stearic acid and 5 mL bioethanol (43.17 MJ/kg). Burning time was tested to observe the quality of the solid bioethanol. The highest calorific value resulted in the longest burning time. The solid bioethanol has a potential as solid fuel due to the significantly higher calorific value compared to the liquid bioethanol. 2019 by the authors.